Worksite Wellness: Improving Physical Activity and Nutrition to Combat Obesity - Bardouche, Kasi (My University, 2020)
Obesity is a growing concern in the workplace setting. About 53% of American workers are considered overweight or obese. There is rise of high sedentary occupational jobs and lack of physical activity in office job settings, increasing the risk of obesity and poor health. Studies have found that Americans work on average 8.5 hours a day with 71% of those hours being sedentary. Through my Applied Practice Experience (APE) at Kansas Department of Health and Environment (KDHE), I created multiple products to help combat obesity through physical activity and nutrition. I created a needs assessment through literature reviews and discussions with employees at KDHE. I followed the CDC’s Workplace Health Model to efficiently incorporate the correct steps to achieve health in the workplace. Ideas and products were created based on achievable outcomes and limitations. Five products were created: Worksite Wellness Policy, Well @ Work Stretching Videos, Complete Streets Legislation, Well @ Work Nutrition Table Tents, and an Action Guide for Government Agencies on the Food and Nutrition Environment. The aim of these products is to increase physical activity and nutrition knowledge and skills to improve employees’ health. Due to the APE timeline the products I created had not yet been fully implemented in the workplace. The future direction is to implement these into the workplace and obtain data to assess the effectiveness of these products.
Keywords: worksite wellness; complete streets; policy; physical activity; nutrition